Cashless Policy and Patronage in Stanbic IBTC Bank Plc, Katsina-Nigeria - Olukorede Olukotun; Oladejo Lukman Golagade; Ahmadu Abubakar (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
Existing empirical literature on cashless banking is one that is quite scanty in the developing countries including Nigeria. Reviews of empirical studies on cashless policy indicate that a lot of prior studies focused on the adoption, prospects and benefits and challenges of cashless policy. This study on the other hand is aimed at investigating the effect of cashless policy on patronage using responses obtained from 410 customers of Stanbic IBTC Plc branch domiciled at Katsina town-Nigeria. To achieve the stated objective, authors used descriptive statistics and multiple regression techniques. The major findings reveal that ATM transaction has significant negative effect on patronage; POS transaction has no significant effect on patronage; web transaction has positive and significant effect on patronage and mobile banking has negative but significant effect on patronage in Stanbic IBTC bank Plc, Katsina. Authors conclude that if deposit money banks in Nigeria can make cashless policy channels well functional and secured, it will enhance and improved bank patronage. It is recommended by the authors that the management of Stanbic IBTC Plc, Katsina needs to ensure that the ATMs are functional 24/7, and loaded with mints to attract patronage. Author also recommends that DMBs should deploy information technology (IT) solutions that will make transactions on POS and other cashless channels more safe and secured. It is also recommended that banks especially Stanbic IBTC Plc should provide incentive for using internet banking platform for transactions; and should deploy mobile banking solution that is all phone enabled.